Secure data collection method of WSN based on mobile Sink - Chunyu MIAO; Yuan FAN; Hui LI; Kaiqiang GE; Xiaomeng ZHANG (网络与信息安全学报)
At present, WSN data collection method based on mobile Sink has some problems, such as low detection rate of network attack and large memory cost, which makes the network vulnerable to network attack and difficult to be applied in practice.To solve this problem, a secure data collection WSN method of WSN based on mobile Sink was proposed, which used convex hull algorithm of energy perception to identify data collection points, used elliptic encryption algorithm (ECC) to generate key for all nodes in the network, used ElGamal algorithm to realize node identity and message authentication, and used support vector machine (SVM) to identify network attack types.The simulation results show that the proposed secure data collection method has good performance in attack detection rate, memory overhead and packet delivery rate.